CFD Analysis of Thermal Distribution and Airflow in a Confined Classroom: RoomE303, Sumatera Institute of Technology - Rizki Anisatul Khasanah; Nike Dwi Grevika Drantantiyas; Titis Pajar Ningsih; Zefanya Frandita Situmorang; Muhammad Fadli Bagaskara (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
This study evaluates the thermal comfort of Classroom E303 at the Sumatera Institute of Technology, a west-facing room exposed to high solar heat in a tropical climate. Air temperature and relative humidity were measured at 16 points under unoccupied conditions and used as boundary inputs for computational fluid dynamics (CFD) simulations developed with SketchUp and SolidWorks. Model validation using mean absolute percentage error (MAPE) and root mean square error (RMSE) showed good accuracy at 4.41% and 1.06 °C. Baseline analysis indicates that the thermal conditions approach the upper limit of the SNI 03-6572-2001 comfort standard, reflecting a warm indoor environment. A mist-based evaporative cooling scenario reduced temperature by 2.7 °C and increased relative humidity by 16%RH, demonstrating its potential to enhance comfort. The findings confirm that CFD is an effective tool for predicting indoor thermal performance and supporting passive, energy-efficient strategies in tropical educational buildings.